Price Setting in Online Markets: Basic Facts, International Comparisons, and Cross-Border Integration - Gorodnichenko, Yuriy; Talavera, Oleksandr (American Economic Review, 2017)
We document basic facts about prices in online markets in the U.S. and Canada, a rapidly growing segment of the retail sector. Relative to prices in regular stores, prices in online markets are more flexible as well as exhibit stronger pass-through (60-75 percent) and faster convergence (half-life less than 2 months) in response to movements of the nominal exchange rate. Multiple margins of adjustment (frequency of price changes, direction of price changes, size of price changes, exit of sellers) are active in the process of responding to nominal exchange rate shocks. Furthermore, we use the richness of our dataset to show that degree of competition, stickiness of prices, synchronization of price changes, reputation of sellers, and returns to search effort are important determinants of pass-through and speed of price adjustment for international price differentials.